Sensory and Acceptance Assessment of Yogurt Containing Probiotic Beads in Thailand - Wunwisa Krasaekoopt,; Atittaya Tandhanskul, (Agriculture and Natural Resources, 2008)
Although the encapsulation technique has been proved to increase the survival of probiotics in yogurt, the sensory and acceptance assessment of yogurt containing probiotic beads has not been reported. In this research, the acceptance assessment of this product was performed by consumers in Thailand and the sensory of products was evaluated by using descriptive analysis. Four hundreds yogurt consumers from Bangkok and the suburbs of Bangkok were recruited. Plain and strawberry yogurts containing probiotics beads were served with the questionnaire to determine the consumer demographic, buying behavior and consumer acceptance. The consumers bought yogurt because of its taste (8.8) and nutrients (8.5). Although the addition of probiotic beads affected the texture characteristics by increasing viscosity and difficulty of swallowing, most of consumers accepted plain (82.3%) and strawberry (94.9%) yogurts with probiotic beads, giving scores for texture and overall acceptability of 6.7 and 6.8 for plain yogurt; and 7.5 and 7.6 for strawberry flavored yogurt. They were also willing to try (92.5%) and buy (89.8%) the products, indicating a potential market exists for yogurts containing probiotic beads in market.